PERBEDAAN EFEKTIFITAS INTERVENSI MCKENZIE DAN DEEP NECK MUSCLE EXERCISE TERHADAP TINGKAT NECK PAIN PADA PEKERJA UKIR DI DESA PETEKEYAN JEPARA - Aziza, Anisa Rahma; Handayani, Prita Adisty; Rusmini, Sri (Jurnal Ilmu Keperawatan Komunitas, 2025)
Abstrack Background: Neck pain indicates that a part of the neck is inflamed, tense, or disturbed, preventing it from functioning normally. Repetitive activities and unergonomic positions for workers will trigger musculoskeletal disorders. Attitudes and unsafe work environments closely correlate with health problems among carving workers, leading to neck pain. Objective: This study aimed to determine the difference in the effectiveness of McKenzie and Deep Neck Muscle Training interventions on the level of neck pain in carving workers in Petekeyan Village, Jepara. Method: This study used a quantitative approach with a pre-experimental design, employing a two-group pretest-posttest design strategy. This study specifically measured the neck pain level in group 1 before and after the McKenzie workout intervention, and also measured the pretest-posttest neck pain in group 2 after engaging in a deep neck muscle intervention exercise. This study included 30 samples and employed a purposive sampling technique. This study used the neck pain disability index (NDI) questionnaire instrument to measure the level of neck pain. The Mann-Whitney test served as the statistical test. Results: This study showed that there is a significant difference between giving McKenzie intervention and deep neck muscle training on the level of neck pain in carving workers in Petekeyan village, Jepara, with a p-value of 0.002 (<0.05). Conclusion: The McKenzie workout intervention is more effective in reducing the level of neck pain.